Lactuca sativa: bioindicador para análise do efeito genotóxico de peçonhas - Palmieri, Marcel José (2016)
Cyto and genotoxicity studies allow the evaluation, understanding and establishment of action mechanisms and the extension of the effects of various toxicants, whether they are physical, chemical or biological. The cytogenotoxic effects of most of the venoms are still largely unexplored. Venom toxins have many uses, including the manufacture of pharmaceuticals, when their effects are well known and it is possible to manipulate their concentrations. Plant models are a good alternative to experiments that use animals as test subjects. Plants germinate easily, are easy to manage and maintain and are not hampered by legal and/or ethical impediments regarding their application. Therefore, this study aim was to show the citogenotoxic effects of the venoms of a scorpion species (Tityus serrulatus), two wasps species (Polybia ocidentalis and P. tedious) and six snakes species (Bothrops atrox, B. jararacussu, B. moojeni, B alternatus, Lachesis muta and Crotalus durissus terrificus) on Lactuca sativa (lettuce) meristematic root tip cells - a model widely used in toxicity with proven efficiency. Significant cito and genotoxic effects were observed for all nine species studied. The results showed that the plant model was efficient in the prospecting of the cytogenotoxic activity of venoms, the results were in accordance to effects observed for human cells. The mechanisms leading to the venoms toxicity was attributed to a series of metabolites, proteases, enzymes and other substances such as mastoporams as well as the neurotoxic actions of the venom interrupting the functioning of ionic channels and inducting and acting directly on the signaling and regulation of oxidative stress.